Overview of junctional complexes during mammalian early embryonic development - Canse, Ceren; Yildirim, Ecem; Yaba, Aylin (Frontiers in Endocrinology, 2023)
Cell-cell junctions form strong intercellular connections and mediate communication between blastomeres during preimplantation embryonic development and thus are crucial for cell integrity, polarity, cell fate specification and morphogenesis. Together with cell adhesion molecules and cytoskeletal elements, intercellular junctions orchestrate mechanotransduction, morphokinetics and signaling networks during the development of early embryos. This review focuses on the structure, organization, function and expressional pattern of the cell–cell junction complexes during early embryonic development. Understanding the importance of dynamic junction formation and maturation processes will shed light on the molecular mechanism behind developmental abnormalities of early embryos during the preimplantation period.